Mandibular periosteal (juxtacortical) chondrosarcoma - Costa,Elisângela Maria Cunha (2009)
Periosteal (juxtacortical) chondrosarcoma (PC) is a well-differentiated malignant cartilage-forming tumor arising from the external bone surface, especially in long bones. The therapy of choice is en-bloc resection and, in general, its prognosis is good. This paper reports a rare case of PC affecting the mandible of a 41-year-old man. The lesion presented as a slow-growing-painless swelling that lasted 2 months. Computed tomography scan showed a tumoral mass arising from the external bone surface, extending into the adjacent soft tissue presenting patchy regions of popcorn-like calcifications. A final diagnosis of PC (grade II) was rendered after biopsy. Hemimandibulectomy was undertaken followed by complementary radiotherapy with 70 Gy. Although no episodes of recurrence or metastasis had been noticed after 18 months of follow-up, the patient died and causa mortis could not be established.